Impact of FERC 661-A and IEEE 1547 on Photovoltaic inverter design - Schauder, C. (2011 IEEE Power and Energy Society General Meeting, 2011)
Photovoltaic (PV) inverters may be subject to different standards and interconnection requirements, depending on their size and interconnection point. PV plants connected at transmission voltage levels may be expected to ride through faults and other disturbances, as expressed in FERC Order 661-A for wind power plants. Islanding detection is not necessary, because customers are not directly served from these plants. On the other hand, PV units connected to distribution feeders are expected to trip automatically during voltage and frequency excursions, as expressed in IEEE Std. 1547. Distribution-connected PV inverters have islanding detection that is designed to meet UL 1741. These conflicting requirements may appear as "wind vs. solar" or "transmission vs. distribution" viewpoints. The impacts on utility-scale PV inverter design and specification are discussed.